Melanoleuca juliannae (Basidiomycota, Tricholomataceae), a new species from subgen. Urticocystis - Antonín, Vladimír; Rimóczi, Imre; Benedek, Lajos; Papp, Viktor; Szarkándi, János Gergő; Dima, Bálint; Nagy, László G.; Papp, Tamás; Ďuriška, Ondrej; Tomšovský, Michal (Phytotaxa, 2014)
A new species, Melanoleuca juliannae is described from Hungary. Its most outstanding character is the presence of a violaceous-blue colour in the stipe base. Sequence comparisons with other Melanoleuca species revealed highly similar but decolourate members of the species, lacking the remarkable colour of the stipe. These specimens are described as Melanoleuca juliannae var. decolorans based on three collections from the Czech Republic and Italy. Detailed macro- and microscopic descriptions of the new species are given. The position of M. juliannae within subgen. Urticocystis was confirmed by DNA sequence data of the ITS region of the nuclear ribosomal RNA gene cluster and translation elongation factor 1-alpha (tef1). Although intra-individual heterogeneity in ITS region was revealed in some specimens of the type variety, the tef1 sequences lack a similar heterogeneity.